Plant-made poliovirus vaccines – Safe alternatives for global vaccination - Bolaños-Martínez, Omayra C.; Strasser, Richard (Frontiers in Plant Science, 2022)
Human polioviruses are highly infectious viruses that are spread mainly through the fecal-oral route. Infection of the central nervous system frequently results in irreversible paralysis, a disease called poliomyelitis. Children under five years are mainly affected if they have not acquired immunity through natural infection or via vaccination. Current polio vaccines comprise the injectable inactivated polio vaccine (IPV, also called the Salk vaccine) and the live-attenuated oral polio vaccine (OPV, also called the Sabin vaccine). The main limitations of the IPV are the reduced protection at the intestinal mucosa, the site of virus replication, and the high costs for manufacturing due to use of live viruses. While the OPV is more effective and stimulates mucosal immunity, it is manufactured using live-attenuated strains that can revert into pathogenic viruses resulting in major safety concerns and vaccine-derived outbreaks. During the last fifteen years, plant-based poliovirus vaccines have been explored by several groups as a safe and low-cost alternative, and promising results in protection against challenges with viruses and induction of neutralizing antibodies have been obtained. However, low yields and a high frequency in dose administration highlight the need for improvements in polioviral antigen production. In this review, we provide insights into recent efforts to develop plant-made poliovirus candidates, with an emphasis on strategies to optimize the production of viral antigens.